Imaging Polarimetry of Geostationary Satellite Express-AM5 - Kosaka, N.; Itoh, Yoichi; Saito, T.; Tozuka, M.; Endo, T.; Ando, T. (Одеські астрономічні публікації, 2020)
This paper reports on the optical imaging polarimetry of geostationary satellite Express- AM5. Precise optical polarimetry was carried out using the Nayuta 2-m telescope at Nishi-Harima Astronom- ical Observatory and a polarimeter. V -band images were continuously taken in 312 minutes. The degree of polarization decreased with time until the minimum phase angle was reached at midnight, and then, it in- creased until morning. This change in the degree of polarization is well explained by the reflection of sun- light from monocrystalline solar panels of the satellite and possibly from other satellite components such as the antenna dishes and/or bus